What is the interference in “verbal interference”? - Gerwien, Johannes; Stutterheim, Christiane von; Rummel, Jan (Acta psychologica, 2022)
Research on the interrelation between language and other components of cognition makes frequent use of verbal interference paradigms. In this, participants are engaged in a primary nonverbal task, while simultaneously repeating non-sense syllables from memory or playback to occupy their articulatory buffer, which is assumed to block internal language use. However, language production involves different subprocesses and levels of representation, and no previous study has explicitly investigated which of these are affected by an occupied articulatory buffer. Thus, the current study addresses the question whether an occupied articulatory buffer significantly interferes with conceptualization. In Experiment 1, speakers name simple objects as fast and as accurately as they can under three conditions. In an interference condition, the verbalization task runs in parallel to a secondary, syllable memorization/recall task, which was expected to induce a situation in which the articulatory buffer temporarily holds phonological information while speakers engage in conceptualization. The articulatory buffer was not occupied in two control conditions. In Experiment 2, speakers performed a similar but more complex task. They verbally responded to visual depictions of actions, again under an interference condition and two control conditions. Results obtained in both experiments suggested no interference. Taken together, the findings suggest that an occupied articulatory buffer does not significantly affect conceptualization.
Gesehen am 17.10.2022
Online verfügbar am 15. Oktober 2022, Artikelversion 15. Oktober 2022